FACTORS AFFECTING OUTSOURCING DECISIONS FOR FACILITY MANAGEMENT SERVICES - Veerakul, Nichakorn (Graduate Program of Universitas Tarumanagara, 2023)
This research aimed to explore factors that affect outsourcing decisions for Facility Management (FM) services in Thailand. It was based on the result of 290 respondents authorized to make decisions on outsourcing Facility Management services. Due to differences in each business field, factors that affect outsourcing decisions were also dissimilar. The goal of decisions, in general, was to choose outsourcing services instead of using in-house resources which reflected business needs in terms of management, strategy, economics, or others to help facilitate and increase the competition level. The results of decision makers' perceptions showed that important factors in different industries considerably varied. The most important factors were management and quality factors which were strongly supported by the Core Competency theory. Meanwhile, the Transaction Cost Economics theory was still significant but not regarded as a top priority for business concerns in the present uncertain period.